The Effect of Knowledge sharing and Organizational Citizenship Behavior on Employee Performance through Innovative Behavior at UPT Asrama Haji Makassar - Alam, Syamsul; Akob, Muh; Idris, Ma’ruf (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study examines the effect of knowledge sharing and Organizational Citizenship Behavior (OCB) on employee performance with innovative behavior as a mediating variable at UPT Asrama Haji Makassar. Using a quantitative explanatory approach, data were collected through structured questionnaires distributed to 125 employees and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The research gap lies in the limited number of studies that examine the relationship between knowledge sharing, OCB, innovative behavior, and employee performance in public sector organizations, particularly in institutions with bureaucratic characteristics and seasonal workloads such as UPT Asrama Haji. The results show that: (1) knowledge sharing has a positive and significant effect on employee performance, (2) knowledge sharing significantly affects innovative behavior, (3) OCB does not significantly affect performance, (4) OCB positively affects innovative behavior, (5) innovative behavior significantly influences employee performance, (6) innovative behavior mediates the effect of knowledge sharing on performance, and (7) innovative behavior mediates the effect of OCB.